Reliability, stress analysis and failure preventation methods in mechanical design - Milestone, Wayne D.; American Society of Mechanical Engineers; International Conference on Realibility, Stress Analysis and Failure Prevention (1980: San Francisco) (New York : The American Society of Mechanical Engineers, 1980)
Papers presented at the International Conference on Realibility and Failure Prevention held in San Francisco in August, 1980